Identifying struggles and challenges faced by Indonesian migrant workers pursuing higher education in Taiwan - Siti Zazak Soraya; Mei-Ying Chen (Intelektual Pustaka Media Utama, 2022)
People in social life often underestimated the presence of migrant workers caused by low skills and lack of education. The decision to continue higher education while working in the host country had tremendous challenges. This study aimed to develop a deeper understanding of the reasons, the problem encountered, and the learning strategies of migrant workers pursuing higher education at Indonesian Open Learning University of Taiwan (Universitas Terbuka Taiwan). There were 11 students participated in this study. This study was descriptive qualitative research, and the interactive model was applied in the analysis method. The data were gathered through in-depth interviews, participant observation, and documentation. The finding of this study revealed that: i) The migrant workers had the high motivation to pursue higher education because they wanted to change the stereotype that they were left behind and to seek a better life when they came back to Indonesia; ii) Inadequate time was the main problem to manage the study time due to the high workload; iii) The learning strategies of migrant workers were peer learning, group discussion, and note-taking. However, Indonesian Open Learning University of Taiwan was the excellent choice for the migrant workers in Taiwan to pursue higher education due to the flexibility of learning.